Pendampingan Pembelajaran Berbasis ICT Bagi Guru SMP/MTs di Kecamatan Samaturu - Nasruddin Nasruddin; Jahring Jahring; Nisa Miftachurohmah (LPPM UNINUS, 2020)
The specific objectives and targets planned in the activity of community service include four things as follows: (1) Identification of essential mathematical concepts that can be taught more easily using ICT-based mathematics learning media. As a criterion, at least 50% of mathematics material in SMP / MTs can be taught with ICT-based learning media. (2) The establishment of a Mathematics Teacher Working Group (KKG) with adequate ability and knowledge in the use of ICT-based learning media. As a criterion, at least 75% of partner teachers have good knowledge in the use of ICT-based learning media in the process of learning mathematics. (3) The existence of innovative and explorative mathematics learning media products with a target of at least 90% of partner teachers mastering the material contained in the instruction module for applying ICT-based learning media. (4) There is an opportunity to develop an entrepreneurial spirit, by producing innovative ICT-based mathematics learning media that has a sale value. The methods used in achieving these objectives are (1) Teachers Working Group (KKG) mathematics with the emphasis of coaching that is mastery of ICT-based learning media that is adequate, is expected to overcome the problems of learning mathematics and be able to be a vehicle in facilitating the development of professionalism of teachers. (2) Provide training to teachers to design ICT-based mathematics learning media and implement them in learning activities.